THE INFLUENCE OF SERVANT LEADERSHIP ON FOLLOWERS’ CREATIVITY WITH CLIMATE FOR CREATIVITY AS MEDIATION - Atmoko, Tsamarah Dzubyanni; Tjahjono, Heru Kurnianto (Jurnal Ekonomi dan Bisnis Airlangga, 2024)
Introduction: As a developing nation, Indonesia persists in its endeavors to boost national growth, including initiatives to support the creative industry through startup companies. This research aims to examine the impact of servant leadership on followers’ creativity, with climate for creativity as the mediating factor. Methods: This research is a quantitative study using primary data obtained through a questionnaire survey from 178 employees working in 73 Indonesian startup companies. The sampling method was purposive sampling. The collected data were then processed and analysed using SEM-PLS. Results: The results revealed the significance of climate for creativity as a full mediator in the relationship between servant leadership and followers’ creativity, meaning that servant leadership has an indirect influence on followers’ creativity through climate for creativity. These findings suggest that leaders who adopt servant leadership styles can enhance followers’ creativity through climate for creativity. Conclusion and suggestion: This study found that servant leadership's impact on startup employees' creativity is fully mediated by the perceived climate for creativity. This implies that by fostering a climate supportive of creativity—through flexible work environments, recognition of creativity, and resource provision—servant leaders indirectly enhance employee creativity. Thus, when servant leaders cultivate a climate for creativity, it boosts the creativity of startup employees in their work.